LEADERSHIP OF MULTICULTURAL LEARNING IN IMPROVING SOCIAL SOCIAL TEACHER COMPETENCY IN THE SURABAYA CITY, INDONESIA - Irsyad, Chamim Rosyidi; Sonhadji, Ahmad; Degeng, I Nyoman Sudana; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The main objective of this research is to describe the leadership of multicultural learning in School Area (cluster school) in Surabaya City. Second, describe the social competence of teachers in the school area in the city of Surabaya. Third, describe the impact of multicultural learning leadership in improving the professional competence of teachers in the school area in the city of Surabaya. This study used a qualitative approach conducted on three School Area in the city of Surabaya. Data collection techniques used include: (1) in-depth interviews; (2) participant observation; and (3) documentation study. The collected data is organized and analyzed repeatedly. Data analysis was conducted in two stages, using individual case study data which consisted of: (1) data reduction, (2) data presentation, and (3) conclusions (withdrawal/verification). The second stage, cross-case data analysis using constant comparative method. To ensure the validity of the data, data validity test, which consists of credibility, transferability, and confirmability. This study yielded the following findings. First, the principal multicultural leadership leadership of the School of Regions is: (1) religious; (2) visionary; (3) democracy; (4) transformational; (5) humanist; (6) innovative; (7) creative; (8) charismatic; And (9) collaborative, (10) inclusive. Second, the teacher’s social competence in the School Area in Surabaya City is: (1) inclusive, objective and non-discriminatory; (2) communicative, effective, empathetic, and polite; (3) adaptative on duty which has socio-cultural diversity; And (4) communicative with the professional community itself and other professions orally and in writing or other forms. Third, the impact of multicultural learning leadership in improving teacher competence in school area in Surabaya City is (1) to improve the quality of communication and teacher interaction effectively with learners; (2) can improve the quality of communication and interaction of teachers effectively with fellow educators and education personnel; (3) to improve the quality of communication and teacher interaction effectively with parents of learners and the surrounding community; and (4), can improve teacher performance related to social competencies that are formulated, encouraged to be objective and non-discriminatory; (5) improving communication quality effectively and empathy with fellow educators, education personnel, parents, and community so that it can have further impact by producing a good and qualified learners output; (6) facilitate teachers to adapt in a duty that has socio-cultural diversity; (7) teachers are encouraged to actively communicate with the professional community themselves and other professions orally and in writing or other forms. This conclusion shows that the teacher can not work alone without regard to the environment and must be aware as an integral part of the academic community in which he serves and serves as well as with the outside community. (8) teachers accustomed to honed environmental sensitivity and continuously discuss with colleagues in solving education and learning problems.